Contemporary capitalism and its crises social structure of accumulation theory for the 21st century - Kotz, David M (David Michael) 1943-; McDonough, Terrence; Reich, Michael (Cambridge New York Cambridge University Press, 2010)
"This volume analyses contemporary capitalism and its crises based on a theory of capitalist evolution known as the social structure of accumulation (SSA) theory. It applies this theory to explain the severe financial and economic crisis that broke out in 2008 and the kind of changes required to resolve it. The editors and contributors make available new work within this school of thought on such issues as the rise and persistence of the "neoliberal," or "free-market," form of capitalism since 1980 and the growing globalization and financialization of the world economy. The collection includes analyses of the U.S. economy as well as that of several parts of the developing world"--Provided by publisher
Introduction: social structure of accumulation theory for the 21st century / Terrence McDonough, Michael Reich, and David M. Kotz -- The state of the art of social structure of accumulation theory / Terrence McDonough -- Social structure of accumulation theory / Victor D. Lippit -- A reconceptualization of social structure of accumulation theory / Martin H. Wolfson and David M. Kotz -- Global neoliberalism and the contemporary social structure of accumulation / David M. Kotz and Terrence McDonough -- Globalization or spatialization? : the worldwide spatial restructuring of the labor process / Michael Wallace and David Brady -- Financialization in the contemporary social structure of accumulation / William K. Tabb -- Global neoliberalism and the possibility of transnational state structures / Emlyn Nardone and Terrence McDonough -- Labor in the contemporary social structure of accumulation / Samuel Rosenberg -- The rise of CEO pay and the contemporary social structure of accumulation in the United States / Robert Boyer -- Social structures of accumulation and the criminal justice system / Susan M. Carlson ... [et al.] -- The social structure of accumulation in South Africa / James Heintz -- Social structures of accumulation and the condition of the working class in Mexico / Carlos Salas -- Social structure of accumulation theory for the Arab world : the economies of Egypt, Jordan, and Kuwait in the regional system / Karen Pfeifer
Includes bibliographical references and index
1
Keywords: Capitalism; Global Financial Crisis, 2008-2009; Saving and investment; United States -- Economic conditions -- 2009-